Besprechung: Ch. Bakirtzis (Hrsg.), Mosaics of Thessaloniki. 4th-14th century, Athens 2012. - FOURLAS, Benjamin; TSAMAKDA, Vasiliki (Byzantina Symmeikta, 2014)
Ch. Bakirtzis (Hrsg.), Mosaics of Thessaloniki. 4th-14th century, Athens 2012, 359 S. + 395 Abb. ISBN 978-960-6878-36-7